1999
DOI: 10.1063/1.123045
|View full text |Cite
|
Sign up to set email alerts
|

Strong normal-incidence infrared absorption in self-organized InAs/InAlAs quantum dots grown on InP(001)

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…At the same time, there is experimental evidence that these effects influence the properties of the studied objects at higher temperatures, up to room temperature. In particular, the intraband-interlevel absorption of infrared radiation with a frequency of 500-800 cm -1 was observed in [31] at 77 and 300 K on arrays of InAs/InAlAs quantum dots grown on the InP(001) substrate. Simulating the kinetics of polariton states in GaN-based microcavities (quantum wells), Malpuech et al [37] (see also references in that work) showed the possibility of a laser effect on such structures at 300 K. More recently, the emission of coherent radiation was experimentally observed in GaAs/GaAlAs column microcavities at 10 K [38] and in structures with microcavities on GaN quantum wells at 300 K [39].…”
Section: Doi: 101134/s0021364010240033mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, there is experimental evidence that these effects influence the properties of the studied objects at higher temperatures, up to room temperature. In particular, the intraband-interlevel absorption of infrared radiation with a frequency of 500-800 cm -1 was observed in [31] at 77 and 300 K on arrays of InAs/InAlAs quantum dots grown on the InP(001) substrate. Simulating the kinetics of polariton states in GaN-based microcavities (quantum wells), Malpuech et al [37] (see also references in that work) showed the possibility of a laser effect on such structures at 300 K. More recently, the emission of coherent radiation was experimentally observed in GaAs/GaAlAs column microcavities at 10 K [38] and in structures with microcavities on GaN quantum wells at 300 K [39].…”
Section: Doi: 101134/s0021364010240033mentioning
confidence: 99%
“…The experiments concerning infrared spectroscopy and photoinduced absorption in magnetic fields and without magnetic field exhibit resonance caused by the transitions between quantized energy levels inside quantum dots and quantum wells, as well as between the split levels and the continuum of the valence or conduction band [6,[29][30][31][32]. Carriers localized inside quantum dots can form bound states with the carriers in the continuum (excitons) or with LO phonons (polarons), which can in turn interact with each other and form collective complexes [4-6, 25, 30-32].…”
Section: Doi: 101134/s0021364010240033mentioning
confidence: 99%
“…To date, IR absorption peaks were observed mostly from the InAs QDs embedded in GaAs substrates, with their peaks ranging from 10 µm to 14 µm [12,13,15,16]. On the other hand, only a few results were reported on the IR characteristics of the QD structures grown on InP substrates [11,14,17]. InAs/InP QDs have been regarded as one of the promising material systems for the fabrication of QDIPs, as well as for fiber-optic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Also, In 0.4 Ga 0.6 As/GaAs QDs have been used in three-color QDIPs, demonstrating IR responses at 3.5, 7.5, and 22 µm for different bias voltages [21]. Other III-V material systems under investigation include InAs/InP QDs [75] and InAs/InAlAs QDs [76] grown on InP substrates and InGaAs/InGaP QDs grown on GaAs substrates [77]. Recent results have demonstrated a mid-IR QDIP (4.7 µm) using In 0.68 Ga 0.32 As/In 0.49 Ga 0.51 P QDs grown on GaAs substrates by MOCVD [78].…”
Section: Alternative Qd Materials Systemsmentioning
confidence: 99%